Amazing pharmaceutical effects and health benefits of bilva leaves in dysfunctional uterine bleedings - SATHIYALATHA SARATHI,; SAI RAMA KRISHNA REDDY, (International Journal of Pharma and Bio Sciences, 2019)
Bilva (Aeglemarmeloscorr) is a historical plant that is used for medicinal purposes since time immemorial. It is often considered to be a sacred tree in India and is believed to be a wish granting tree by local people. Bilva has been a therapeutic in a wide range of ailments in Ayurveda. The present insight on the ethnomedicinal usage of the Bilva leaves on large group disorders warrants the need for systematic clinical research to ascertain its properties and mode of action. The products obtained from Bilva, possess is highly nutritive and therapeutic value and hence are getting popularized in India as well as in the international market. The footprint of bilva leaves is identified since the Vedic period. It is botanically identified as Aeglemarmeloscorr which is one of the best virtues of treating dysfunctional uterine bleeding. Dysfunctional uterine bleeding is irregular uterine bleeding that occurs in the absence of recognizable pelvic pathology, general medical conditions or pregnancy. It reflects a disruption in the normal cyclic-pattern of ovulatory hormones. Any de-arrangements in the structure of the uterus such as (leiomyoma, adenomyosis, malignancy or hyperplasia), de-arrangements to the clotting pathways (coagulation or iatrogenically), or disruption of hypothalamic-pituitary-ovarian axis (through ovulatory/endocrine disorders or iatrogenically) can affect menstruation. The study was aimed to analyse the medicinal benefits of bilva leaves for dysfunctional uterine bleeding. The study was conducted among 25 samples between the age group of 17-55 years who had dysfunctional uterine bleeding due to three medical conditions such as women with fibroid uterus, adolescent girls with hormonal imbalance and polycystic ovarian syndrome. The qualitative research approach was adopted in this study. The major findings of the study were the heavy menstrual bleeding was gradually controlled and completely stopped after 5-7 days of consuming the Bilva leaves. Also, Bilva leaves found to be a very effective medicinal virtue for dysfunctional uterine bleeding.